2016
DOI: 10.1177/1352458516638746
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and prevalence of multiple sclerosis in east London

Abstract: MS prevalence was considerably lower among Black and South Asian populations, compared to the White population, by 59% and 84%, respectively. However, compared to available data in Africa and South Asia, MS is several times more prevalent among Black people and South Asians living in the United Kingdom than their territorial ancestry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 30 publications
2
13
1
Order By: Relevance
“…MS cases were defined as individual records containing both a coded diagnosis of MS and a date of diagnosis . Patients with a diagnosis but no date of diagnosis were excluded as both cases and potential controls.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…MS cases were defined as individual records containing both a coded diagnosis of MS and a date of diagnosis . Patients with a diagnosis but no date of diagnosis were excluded as both cases and potential controls.…”
Section: Methodssupporting
confidence: 88%
“…The increased odds of MS in the young Black population speaks to the importance of performing rigorous epidemiological studies with adequate representation from BAME groups. Worryingly, the recently published global prevalence estimates may be an underestimate when our findings are considered …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Puerto Ricans tend to be affected by vitamin D insufficiency/deficiency despite abundant sunlight [8]. In addition, European ancestry has been shown to increase the likelihood of developing MS [28, 29]. The genetic makeup of Puerto Ricans has a higher African American and European ancestry mixture than that of Mexican Americans [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Demographics data stored in EMR enabled researchers to also study differences in the incidence or prevalence of MS over time, or among different populations based on ethnicity, sex or geographic location. For example, it has been observed that there is a higher incidence of MS in children of African ancestry compared with children of European ancestry, a lower prevalence of MS among populations of African and Asian ancestries compared with a population of European ancestry in London, a similar prevalence of the disease in a district of Spain compared with the prevalence reported in other regions in Spain and a slight increase of MS in recent years in the Netherlands, especially among women . Environmental studies are also possible with EMR data, with one study suggesting that air pollution might have a role in determining MS occurrence and relapses .…”
Section: Use Of Electronic Medical Records In Multiple Sclerosis Resementioning
confidence: 99%